Clinical utility of plasma Aβ42/40 ratio by LC-MS/MS in Alzheimer’s disease assessment - Weber, Darren M.; Taylor, Steven W.; Lagier, Robert J.; Kim, Jueun C.; Goldman, Scott M.; Clarke, Nigel J.; Vaillancourt, David E.; Duara, Ranjan; McFarland, Karen N.; Wang, Wei-en; Golde, Todd E.; Racke, Michael K. (Frontiers in Neurology, 2024)
Introduction Plasma Aβ42/40 ratio can help predict amyloid PET status, but its clinical utility in Alzheimer’s disease (AD) assessment is unclear. Methods Aβ42/40 ratio was measured by LC-MS/MS for 250 specimens with associated amyloid PET imaging, diagnosis, and demographic data, and for 6,192 consecutive clinical specimens submitted for Aβ42/40 testing. Results High diagnostic sensitivity and negative predictive value (NPV) for Aβ-PET positivity were observed, consistent with the clinical performance of other plasma LC-MS/MS assays, but with greater separation between Aβ42/40 values for individuals with positive vs. negative Aβ-PET results. Assuming a moderate prevalence of Aβ-PET positivity, a cutpoint was identified with 99% NPV, which could help predict that AD is likely not the cause of patients’ cognitive impairment and help reduce PET evaluation by about 40%. Conclusion High-throughput plasma Aβ42/40 LC-MS/MS assays can help identify patients with low likelihood of AD pathology, which can reduce PET evaluations, allowing for cost savings.